Response of a Coastal Microbial Community to Olivine Addition in the Muping Marine Ranch, Yantai - Ren, Hongwei; Hu, Yubin; Liu, Jihua; Zhang, Zhe; Mou, Liang; Pan, Yanning; Zheng, Qiang; Li, Gang; Jiao, Nianzhi (Frontiers in Microbiology, 2022)
Spreading olivine powder in seawater to enhance alkalinity through weathering reactions has been proposed as a potential solution to control atmospheric CO2 concentration. Attention has usually been paid to the chemical properties of seawater after the addition of olivine within lab and modeling studies. However, both microbial acclimation and evolution in such manipulated natural environments are often overlooked, yet they are of great importance for understanding the biological consequences whether olivine addition is a feasible approach to mitigating climate change. In this study, an olivine addition experiment was conducted to investigate variation in bacterial diversity and community composition in the surface and bottom seawater of a representative marine ranch area on the south coast of the Bohai Sea. The results show that the composition of the particle-attached microbial community was particularly affected by the application of olivine. The relative abundance of biofilm-forming microbes in particle-attached fraction increased after the addition of olivine, while no significant variation in the free-living bacterial community was observed. Our study suggests that olivine addition would reshape the bacterial community structure, especially in particle-attached microenvironments. Therefore, the risk evaluation of alkalinity enhancement should be further studied before its large-scale application as a potential ocean geoengineering plan.